Community rehabilitation in neurology - Barnes, Michael P., 1952-; Radermacher, Harriet, 1975- (Cambridge, UK ; New York : Cambridge University Press, 2003)
Analyses community rehabilitation needs from many different perspectives. Many examples of community rehabilitation schemes are presented, and case studies are used to highlight the main issues. The authors take an international view, and there are chapters dealing with the disabled child in the community and with neuropsychological rehabilitation.
Cover; Half-title; Title; Copyright; Contents; 1 Background to community neurological rehabilitation; 2 Neurological rehabilitation -- basic principles and models of delivery; 3 Models of disability; 4 Concepts of community; 5 The views of disabled people; 6 Outcome measures and research in the community; 7 Evidence base for community neurological rehabilitation; 8 Lessons from the South; 9 Other aspects of community neurological rehabilitation; 10 Community rehabilitation in childhood: concepts to inform practice; 11 Neuropsychological rehabilitation in the community; 12 The way forward.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 24, 2025).
eBooks on EBSCOhost
Keywords: Nervous system -- Diseases -- Patients -- Rehabilitation; Community health services; Nervous System Diseases -- rehabilitation; Community Health Services; Système nerveux -- Maladies -- Patients -- Réadaptation.; Services communautaires de santé.; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Community health services; Nervous system -- Diseases -- Patients -- Rehabilitation